Le développement des algues macrophytes le long du littoral roumain pendant les années 1977 et 1978 - Skolka, Hilarius V.; Vasiliu, Florian; Bologa, Alexandru S. (Cercetări Marine - Recherches Marines, 2026)
Quantitative dynamics of the macrophyte communities along the Romanian Black Sea shores (rocky mid- and infralittoral), during 1977 and 1978, was analyzed. The production of seaweeds evinced the following values during 1977: 4,272g/m2 (Agigea), 11,352g/m2 (Eforie Sud) and 14,793g/m2 (Vama Veche). An increase of algal biomasses with depth (3m) is generally found.